2022
DOI: 10.1038/s41598-022-06593-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal communities affect the chemical quality of flue-cured tobacco leaves in Bijie, Southwest China

Abstract: Soil microorganisms could affect the quality of tobacco leaves, however, little is known about the association of tobacco chemical components and soil fungal communities. In the present study, the relationship between soil fungi and tobacco quality based on chemical components in Bijie was investigated. The results showed that the total harmony scores (THS) of the analyzed tobacco leaves ranged from 46.55 ± 3.5 to 91.55 ± 2.25. Analyses of chemical components revealed that high contents of nicotine (≥ 1.06%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
10
3
Order By: Relevance
“…Trichoderma species are popular biocontrol agents as well as significant growth-promoting orchid plants ( Gutiarrez-Miceli et al, 2008 ; Yuan et al, 2009 ). Saitozyma degrades plant cellulose ( Wang et al, 2022 ). Therefore, our data show that litter-or wood-decaying fungi, such as Mortierella , Chaetomium , Trichoderma , Fusarium , and Saitozyma species, may provide carbon and nutrients to the symbiotic fungi of Gastrodia species.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma species are popular biocontrol agents as well as significant growth-promoting orchid plants ( Gutiarrez-Miceli et al, 2008 ; Yuan et al, 2009 ). Saitozyma degrades plant cellulose ( Wang et al, 2022 ). Therefore, our data show that litter-or wood-decaying fungi, such as Mortierella , Chaetomium , Trichoderma , Fusarium , and Saitozyma species, may provide carbon and nutrients to the symbiotic fungi of Gastrodia species.…”
Section: Discussionmentioning
confidence: 99%
“…Some research studies paid attention to the effects of the nitrogen-reducing strategy on fungal community of food crops such as wheat, rice, and maize ( Wen et al, 2020 ; Liu et al, 2021 ; Wang et al, 2021 ). Wang et al found that Humicola , Tausonia , and Codinaea could improve the chemical quality of tobacco ( Wang et al, 2022 ). Nevertheless, few had focused on the fungal inhibitory effect of nitrogen-reducing fertilization on tobacco diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Good soil conditions are needed for high-quality tobacco production ( Mallikharjuna Rao et al, 2016 ; Begum et al, 2021 ; Shen et al, 2022 ). To achieve sustainable tobacco production, soil quality must be improved ( Wang et al, 2019 ; Yan et al, 2019 ; Wang et al, 2022 ). However, due to the extensive use of chemical fertilizer and a series of bad farming measures in tobacco planting regions, the soil microbial abundance and diversity have been reduced, leading to soil acidification, hardening, fertility decline and other outstanding problems, which not only seriously affect crop yield but also adversely affect the sustainable development within the ecosystem and the green environment ( Wang Q. et al, 2017 ; Kavamura et al, 2018 ; Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%